MicroRNA-23a-3p overexpression represses proliferation and accelerates apoptosis of granular cells in polycystic ovarian syndrome by targeting HMGA2 - Junzi Wei; Ping Cheng; Mei Kong; Ling Zhang; Shuang Liu; Bingxue Ning; Xinlin Huang (Taylor & Francis Group, 2023)
Objective Granular cells (GCs) are involved in polycystic ovarian syndrome (PCOS) progression. MicroRNA (miR)-23a downregulation is linked to PCOS development. Therefore, this research explored the influences of miR-23a-3p on GC proliferation and apoptosis in PCOS.Methods Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting were conducted to examine miR-23a-3p and HMGA2 expression in GCs of patients with PCOS. Then, miR-23a-3p and/or HMGA2 expression was altered in GCs (KGN and SVOG), after which miR-23a-3p, HMGA2, Wnt2, and β-catenin expression, GC viability, and GC apoptosis were measured by RT-qPCR and western blotting, MTT assay, and flow cytometry, respectively. A dual-luciferase reporter gene assay was utilized to assess the targeting relationship between miR-23a-3p and HMGA2. Finally, GC viability and apoptosis were tested after the combined treatment of miR-23a-3p mimic and pcDNA3.1-HMGA2.Results miR-23a-3p was poorly expressed but HMGA2 was overexpressed in GCs of patients with PCOS. Mechanistically, HMGA2 was negatively targeted by miR-23a-3p in GCs. Furthermore, miR-23a-3p inhibition or HMGA2 upregulation elevated viability and reduced apoptosis of KGN and SVOG cells, along with increased Wnt2 and β-catenin expression. In KNG cells, HMGA2 overexpression abrogated the impacts of miR-23a-3p overexpression on GC viability and apoptosis.Conclusions Collectively, miR-23a-3p decreased HMGA2 expression to block the Wnt/β-catenin pathway, thereby depressing viability and facilitating apoptosis of GCs.